Experimental Performance Test of Key Components of the KATRIN Outer Tritium Loop. (3rd April 2017) - Welte, S.; Fanghänel, E.; Fischer, S.; Kramer, F.; Le, T. L.; Sturm, M.; Tuchscherer, N.
Abstract: One of the main tasks of the Tritium Laboratory Karlsruhe (TLK) is the operation of the Windowless Gaseous Tritium Source (WGTS) of the Karlsruhe Tritium Neutrino (KATRIN) experiment, which will perform an absolute measurement of the neutrino mass with a sensitivity of 200 meV/c 2 (90% confidence level). While the Inner Loop system of KATRIN provides a stabilized tritium throughput of 40 g day −1 in the WGTS, the outer loop is required for tritium clean-up, purification, and accountancy. The ability of the outer loop to supply tritium has been investigated using feed gas samples of different compositions. This paper will describe the gas processing tests which were done with batches of approximately 1 mol of tritium each and 20 mol in total, processed on a day-to-day basis in the TLK tritium loop. It is shown, that an isotopic tritium purity of > 98% can reliably supplied to the KATRIN experiment. This is sufficient to maintain the required isotopic tritium purity of > 95% in the KATRIN inner loop.